The Impact of Marketing Mix (7P’s) Towards Fish Feed Customer Satisfaction of PT. Central Proteinaprima in Sidoarjo Area - Yohannes Santoso (iBuss Management, 2015)
Customer satisfaction is one of the crucial factors that determines the performance of a company. In Sidoarjo, PT. Central Proteinaprima competes with another companies to control the animal feed market. This research was conducted to determine the effect of the marketing mix (7P's) towards customer satisfaction. Data obtained using simple random sampling method by distributing questionnaires to 132 respondents in Sidoarjo. Data then analyzed using Multiple Linear Regression Analysis. Results from this study indicate that the marketing mix (7P's) overall has significant influence towards fish feed customer satisfaction of PT. Central Proteinaprima in Sidoarjo. Individually, the price has a significant influence on fish feed customer satisfaction of PT. Central Proteinaprima in Sidoarjo. Keywords: Marketing mix, Customer satisfaction